Eugenol Attenuates Cerebral Ischemia-Reperfusion Injury by Enhancing Autophagy via AMPK-mTOR-P70S6K Pathway - Sun, Xiaowei; Wang, Dongyan; Zhang, Tingting; Lu, Xuejian; Duan, Fangfang; Ju, Lili; Zhuang, Xiaotong; Jiang, Xicheng (Frontiers in Pharmacology, 2020)
Eugenol, as an active compound isolated from Acorus gramineus, has been shown to protect against cerebral ischemia-reperfusion (I/R) injury. Nonetheless, the detailed neuroprotective mechanisms of eugenol in cerebral I/R injury have not been elaborated. In the present study, cerebral I/R injury model was established by middle cerebral artery occlusion (MCAO) in rats. HT22 cells were subjected to oxygen-glucose deprivation/reperfusion (OGD/R) to mimic cerebral I/R injury in vitro. The results showed that eugenol pre-treatment relieved cerebral I/R injury as evidenced by improving neurological deficits and reducing infarct volume. Autophagy was induced by MCAO, which was further promoted by eugenol administration. Moreover, rapamycin, an activator of autophagy, promoted eugenol-induced decreases in neurological score, infarct volume, brain water content, and apoptosis. However, pre-treatment with 3-MA, an inhibitor of autophagy, led to the opposite results. Similarly, eugenol pre-treatment increased the viability and restrained apoptosis of OGD/R-challenged HT22 cells. OGD/R-induced autophagy was strengthened by eugenol. Mechanically, eugenol promoted autophagy through regulating AMPK/mTOR/P70S6K signaling pathway in vivo and in vitro. In conclusion, pretreatment with eugenol attenuated cerebral I/R injury by inducing autophagy via AMPK/mTOR/P70S6K signaling pathway.